Rancangan Media Promosi Perpustakaan di Perpustakaan Universitas Negeri Padang - Moprita, Tischa; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
This article aims to describe the design of promotional library media in Universitas Negeri Padang Library. Data collected through direct observation and interviews with Employees Universitas Negeri Padang Library, as well as literature using books and reading are considered important. Analyzing data descriptively. Based on analyzing the data, it was concluded library media campaign can be designed using CorelDraw application program. The aspects that must be considered and should be made is the physical form, illustration, text, typography, and color. The draft media campaign should be designed to attract. Use short sentences, clear, solid, and are important information. Media campaigns can be designed is a brochure, bookmarks, calendars library, libraries pins, bags library, library glasses, clothes library, library umbrellas and posters. Keywords: design; promotional library media